FENOMENOLOGI KOMUNIKASI TERAPEUTIK FAMILY CAREGIVER KOMUNITAS PEDULI SKIZOFRENIA INDONESIA (KPSI) - Shofia Nur Rahma; Rini Riyantini; Dian Tri Hapsari (Universitas Prof. Dr. Moestopo (Beragama), 2021)
Therapeutic communication has an important role to help the recovery process of People With Schizophrenia (ODS) who have symptoms of hallucinations and delusions that can lead to a tendency to have difficulty communicating to withdraw from the social environment. Therapeutic communication is a form of communication aimed at the therapeutic process and patient healing. Phenomenology is used as a method and therapeutic communication as a theory in this study. The data collection method was carried out through online interviews using WhatsApp voice calls to 6 ODS family caregiver informants. The results of this study indicate that the experience of therapeutic communication carried out by family caregivers in the form of interpersonal communication can help the ODS awareness process regarding schizophrenia as indicated by ODS' willingness to take medication regularly, as well as communication in the form of showing acceptance, listening carefully, and emotional regulation when communicating with ODS can provide appropriate treatment when ODS has relapse symptoms so that it can help the process of developing ODS.